Pengaruh Media Edukasi Video Animasi Rells dan Leaflet terhadap Pengetahuan Pencegahan Stunting pada Remaja di SMA Kesatrian 1 Semarang - Muhammad Hanun Nizar; Indra Tri Astuti; Herry Susanto (Journal of Health, Medical, and Psychological Studies, 2025)
Stunting remains a major public health problem that requires early preventive efforts, including health education targeting adolescents. This study aimed to analyze the effect of animated video reels and leaflet media on adolescents’ knowledge regarding stunting prevention at SMA Kesatrian 1 Semarang. A quasi-experimental design with a two-group pretest–posttest approach was applied, involving 140 students divided into an intervention group and a control group. The intervention group received health education using animated video reels, while the control group received leaflet-based education. Knowledge levels were measured using a validated questionnaire before and after the intervention. The Wilcoxon test showed a significant increase in knowledge in both groups, with a p-value of 0.000 in the intervention group and 0.001 in the control group. The Mann–Whitney U test revealed a significant difference in knowledge improvement between groups (p = 0.004), with a higher median score increase in the intervention group. These findings indicate that animated video reels are more effective than leaflets in improving adolescents’ knowledge of stunting prevention. Integrating digital-based educational media is recommended to strengthen school-based stunting prevention programs